Pengaruh Kepemimpinan Transaksional, Motivasi Intrinsik, dan Dukungan Sosial terhadap Kinerja Karyawan PT Metaform Purwakarta - Ernawati, Ernawati; Intan Rahma Azhari; Tiara Putri Pratama; Anne Rufaidah Alief; Eteh Resa Asyifa (MAMEN: Jurnal Manajemen, 2025)
Employee performance is an important aspect that determines the success of a company, including at PT. Metaform in Purwokerta. This study is motivated by the importance of understanding the factors that influence employee performance, especially transactional leadership, intrinsic motivation, and social support. Transactional leadership is believed to be able to provide clear direction and rewards for employees, while intrinsic motivation encourages employees to work optimally because of the drive from within. In addition, social support from coworkers and superiors can also increase self-confidence and work enthusiasm. The purpose of this study was to analyze the effect of transactional leadership, intrinsic motivation, and social support on employee performance at PT. Metaform Purwokerta. The study was conducted using a quantitative method by distributing questionnaires to 60 employees of PT. Metaform. The data were analyzed using multiple regression to determine the effect of the three independent variables on employee performance. The results showed that transactional leadership, intrinsic motivation, and social support together had a positive and significant effect on employee performance. These findings are recommendations for company management to strengthen transactional leadership practices, increase employee intrinsic motivation, and strengthen social support in the work environment.